Profiling sugar metabolism during fruit development in a peach progeny with different fructose-to-glucose ratios - Desnoues, Elsa (BMC Plant Biol, 2014)
BACKGROUND: Fruit taste is largely affected by the concentration of soluble sugars and organic acids and non-negligibly by fructose concentration, which is the sweetest-tasting sugar. To date, many studies investigating the sugars in fruit have focused on a specific sugar or enzyme and often on a single variety, but only a few detailed studies addressing sugar metabolism both as a whole and dynamic system are available. In commercial peach fruit, sucrose is the main sugar, followed by fructose and glucose, which have similar levels. Interestingly, low fructose-to-glucose ratios have been observed in wild peach accessions. A cross between wild peach and commercial varieties offers an outstanding possibility to study fruit sugar metabolism. RESULTS: This work provides a large dataset of sugar composition and the capacities of enzymes that are involved in sugar metabolism during peach fruit development and its genetic diversity. A large fraction of the metabolites and enzymes involved in peach sugar metabolism were assayed within a peach progeny of 106 genotypes, of which one quarter displayed a low fructose-to-glucose ratio. This profiling was performed at six stages of growth using high throughput methods. Our results permit drawing a quasi-exhaustive scheme of sugar metabolism in peach. The use of a large number of genotypes revealed a remarkable robustness of enzymatic capacities across genotypes and years, despite strong variations in sugar composition, in particular the fructose-to-glucose ratio, within the progeny. A poor correlation was also found between the enzymatic capacities and the accumulation rates of metabolites. CONCLUSIONS: These results invalidate the hypothesis of the straightforward enzymatic control of sugar concentration in peach fruit. Alternative hypotheses concerning the regulation of fructose concentration are discussed based on experimental data. This work lays the foundation for a comprehensive study of the mechanisms involved in sugar metabolism in developing fruit. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12870-014-0336-x) contains supplementary material, which is available to authorized users.